Factors influencing consumer behavioural intention and their effects on behaviour and willingness to pay for green hotels in Malaysia - Moghadas, Shayesteh (2017)
Malaysia is one of the favourite destinations of tourists around the world; the numbers of tourists who visit this country increases gradually. Nowadays, environmental problems are discussed considerably, and people are starting to be aware of conservation activities. In the hotel industry, green hotel is becoming a new trend that can attract guests who are concerned about the environment and intend to be involved in green practices. The general objective of this study is to investigate the relationship of attitude, subjective norms, perceived behavioural control, and perceived value with behavioural intention and its influence on behaviour and willingness to pay. The target population of this study was 329 domestic and international tourists, who visited green hotels in Malaysia during the survey period. The collected data were statistically analysed using SPSS 21 and AMOS 21. The findings of this study support the hypothesized relationship proposed in the theoretical model. Specifically, the result of Structural Equation Model revealed a relationship between TPB model, perceived value and guests’ behaviour toward selecting green hotels in Malaysia. The results of the specific hypotheses tests indicate a significant relationship between the behavioural intentions and behavioural, willingness to pay of guests who selecting green hotels. This study contributes new knowledge on the relationship between TPB and the behavioural intention and behaviour of guests toward green hotels. The study also extends the literature regarding the effect of the perceived value of guests on their behavioural intention and behaviour toward selecting green hotels in Malaysia. The study can benefit hotel marketers, especially those of green hotels, in their understanding of what tourists want and need. The findings of this study guide the designing of effective marketing strategies to increase consumer behavioural intention as well as to influence current tourists’ intention to return and recommend green hotels in Malaysia to others.